Автоматизированная информационная система комплексной оценки финансовой устойчивости коммерческих банков - Рзаев, Р.Р.; Бабаева, С.Т.; Бабаев, Т.А. (Проблемы управления и информатики, 2017)
Розглянуто підхід до створення автоматизованої інформаційної системи оцінки фінансової стійкості комерційних банків на основі застосування нечітких методів багатокритеріальної оцінки і ранжування альтернатив. У контексті даного дослідження розроблено методику оцінки фінансових показників комерційних банків на поточний період їх фінансової діяльності. Апробація запропонованої методики проводиться на прикладі фінансових звітностей чотирьох довільно взятих комерційних банків. It is proposed an approach to the creation of the automated information system of financial stability estimation of commercial banks on the basis of fuzzy forecasting methods, multicriteria evaluation and ranking of alternatives. In the context of this study it is developed a method of evaluating financial performance of commercial banks for current period of their financial activities. Testing of the proposed method is carried out on the example of the financial statements of four arbitrary commercial banks.